Konsep “Pluralisme Agama” Dalam Al-Quran (Aplikasi Semiotika Roland Barthes Terhadap Qs. Al-Baqarah [2]: 62) - Abdul Rohman (LPPAIK Universitas Muhammadiyah Bandung, 2021)
This article discusses to the concept of “religion pluralism”in the Qurán which is found Q.S Al-Baqarah [2]: 62. This paper aims to answer several questions about how the application of Roland Barthes’ semiotics to the concept of “religious pluralism”in the Koran, display the message that the verse is trying to convey, the ideology he built and does the Koran admit the axistence of religious pluralism. The purpose of this paper is to seek knowledge about the structure of the text in Koran Al-Baqarah [2]: 62 and the message contained in the verse using Roland Barthes’ semiotic theori approach. The writing of this research uses a qualitative method based on a literature review. The results obtained in the verse are that Q.S Al-Baqarah [2]: 62 according to the linguistic sytem it is defined as adherents of heavenly religion and the only religion that will survive after tha prophet Muhammad was sent is Islam. While the mythological sytem is that the Koran acknowledges the existence of religious plurality, but does not recogniz the axistence of religious pluralism. The ideology is builds is religious exclusivity in the context of its interactions with other religious.